2018
DOI: 10.1016/j.jcrs.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Interface morphology and gas production by a refractive 347 nm ultraviolet femtosecond laser: Comparison with established laser systems

Abstract: Ultraviolet laser lenticule extraction seems promising. The interface quality was similar to that of the clinical Visumax system while gas production was reduced significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…40 The gas bubble produced from the first pass might expand and displace the collagen fibrils; this could cause the second pass to deviate from the planned incision and increase the refractive variation. 41 Two eyes (9%) had undercorrection of up to À2.00 diopters (D) after immediate re-SMILE. 6 Although waiting 1 hour to 2 hours after suction loss for the resolution of gas bubble before attempting re-SMILE may increase the accuracy of the second pass, the authors reported 100% of the eyes in the suction loss group were within ±1.00 D of the target correction after same-day re-SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…40 The gas bubble produced from the first pass might expand and displace the collagen fibrils; this could cause the second pass to deviate from the planned incision and increase the refractive variation. 41 Two eyes (9%) had undercorrection of up to À2.00 diopters (D) after immediate re-SMILE. 6 Although waiting 1 hour to 2 hours after suction loss for the resolution of gas bubble before attempting re-SMILE may increase the accuracy of the second pass, the authors reported 100% of the eyes in the suction loss group were within ±1.00 D of the target correction after same-day re-SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-short ultraviolet (UV) pulses with high peak power have a wide range of applications in material processing [1], biology [2], spectroscopy [3], ultrafast molecular dynamics [4], and so on. In the field of Free Electron Laser (FEL) [5], to match the emitting requirement of photocathode, high power ultrashort pulse at UV wavelength range are often used as the driving laser source [5].…”
Section: Introductionmentioning
confidence: 99%